Acute blood pressure responses of hypertensive patients after multimodal training session: Protocol study - Silva de Sousa, Gabriel; Cardosos Santos, José Wilhan; Martins da Cunha, Raphael (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Systemic arterial hypertension (SAH), as well as other chronic degenerative diseases, has been growing around the world. In this context, physical exercise is presented as a non-pharmacological strategy both in the treatment and in the prevention of this disease. Although pressure responses to strength and aerobic exercise are vast in the literature, in high-intensity multimodal exercises they are very scarce. Objectives: To develop a study protocol on the acute effects of blood pressure after a high-intensity multimodal training session in adult hypertensive individuals through a randomized crossover clinical trial. Methods: This is a controlled crossover clinical trial to evaluate the acute responses of blood pressure after a multimodal training session in hypertensive patients. 20 hypertensive adults will be recruited, who, after inclusion in the study, will perform 02 protocols with an interval of 07 days, one session of high-intensity multimodal exercises, and a control session (without exercises). Blood pressure (BP) will be measured before, immediately after, and for 60 minutes after carrying out the protocols. Results: The designed intervention is expected to provide additional information on the behavior of (BP) hypertensive individuals in the practice of multimodal exercises.